Clinical characteristics of COVID‐19 in hospitalized young infants and risk factors for disease severity - Ng, David Chun‐Ern; Tan, Kah Kee; Liew, Chuin Hen; Low, Yik Wan; Chin, Ling; Jamil, Munzir Bin; Chandirasekharan, Debashini a/p; Baharuddin, Suhaila Binti; Cheah, Yee Keat (Pediatrics international, 2023)
Background This study aimed to describe the clinical characteristics and severity of young infants hospitalized with COVID‐19 and study the relationship between breastfeeding and maternal COVID‐19 vaccination on the severity of COVID‐19. Methods A retrospective, observational study was performed among infants aged 6 months and below hospitalized for COVID‐19 in a tertiary state hospital in Malaysia between February 1 and April 30, 2022. The primary outcome was “serious disease,” defined as pneumonia requiring respiratory support or dehydration with warning signs. Multivariate logistic regression was used to determine independent predictors for serious disease. Results A total of 102 infants were included in the study; 53.9% were males with a median age of 11 weeks (interquartile range: 5–20 weeks). Sixteen patients (15.7%) had pre‐existing comorbidities, including preterm birth. Fever was the most common presenting symptom (82.4%), followed by cough (53.9%), and rhinorrhea (31.4%). Forty‐one infants (40.2%) presented with serious disease, warranting either respiratory support or intravenous fluid therapy for dehydration. Recent maternal COVID‐19 vaccination was associated with a reduced risk of serious disease on univariate analysis but was not significant after multivariate adjustment (adjusted odds ratio [aOR] 0.39; 95% CI: 0.14–1.11; p = 0.08). Exclusive breastfeeding was protective against serious COVID‐19 in young infants, independent of other confounding factors (aOR 0.21, 95% CI: 0.06–0.71; p = 0.01). Conclusion COVID‐19 is a serious disease with non‐specific clinical manifestations in young infants. Exclusive breastfeeding could play an important protective role.